2010
DOI: 10.1590/s1516-05722010000300007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da atividade cicatrizante do jucá (Caesalpinia ferrea Mart. ex Tul. var. ferrea) em lesões cutâneas de caprinos

Abstract: RESUMO:O objetivo deste estudo foi demonstrar os efeitos do tratamento tópico do jucá (Caesalpinia ferrea) em feridas cutâneas. Quinze caprinos machos sem raça definida foram divididos em 3 grupos de acordo com o pós-cirúrgico (7 o , 14 o e 21 o dias). As feridas experimentais foram tratadas com a pomada composta pela casca da Caesalpinia ferrea em pó misturada com a vaselina estéril e as do grupo controle apenas com a vaselina esterilizada. A aplicação diária da pomada e da vaselina estéril foi realizad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 10 publications
(3 reference statements)
0
24
0
13
Order By: Relevance
“…O percentual de contração é um parâmetro morfométrico frequentemente utilizado como indicador de resolução do processo cicatricial (BATISTA et al, 2010). Esse fenômeno ocorre devido à diferenciação dos fibroblastos em miofibroblastos que apresentam capacidade contrátil e promovem força de tensão e união dos bordos da ferida (OLIVEIRA et al, 2010).…”
Section: Resultsunclassified
“…O percentual de contração é um parâmetro morfométrico frequentemente utilizado como indicador de resolução do processo cicatricial (BATISTA et al, 2010). Esse fenômeno ocorre devido à diferenciação dos fibroblastos em miofibroblastos que apresentam capacidade contrátil e promovem força de tensão e união dos bordos da ferida (OLIVEIRA et al, 2010).…”
Section: Resultsunclassified
“…Previous studies have shown biological activities of the extracts of fruit and stem L. ferrea, such as antiinflammatory (Carvalho et al 1996;Pereira et al 2012), and antimicrobial, whereas fruit extract can inhibit in vitro growth of oral pathogens (Sampaio et al 2009), and antioxidant (Silva et al 2011), but this was the first screening with different extracts obtained from L. ferrea evaluated for Leishmania species. However, previous studies showed that the topical use of L. ferrea ointment was significantly efficient to help healing cutaneous wounds in goats (Oliveira et al 2010). Studies that seek new therapeutic forms against cutaneous leishmaniasis evaluate several parameters to determine the efficacy of the compound and its use (Schwartz et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Libidibia ferrea has a wide distribution, and many economic and pharmacological properties, being used from wood production to the afforestation of streets and avenues (Souza and Lorenzi 2012). Pharmacological studies of extracts obtained from L. ferrea have demonstrated its biological anti-inflammatory (Carvalho et al 1996), bactericidal (Sampaio et al 2009), hypoglycemic and antioxidant potentials (Batubara et al 2009) and healing activity (Oliveira et al 2010). Chemical studies with this species have shown the presence of phenolic compounds with possible pharmacological applications, such as chalcones and polyphenols (Nakamura et al 2002;Nozaki et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Healing assays using experimental animals, particularly those assessing wound healing promoter substances, are conducted worldwide (LOPES et al, 2005;OLIVEIRA et al, 2010;NAYAK et al, 2011). Wound contraction is frequently assessed in these experiments because it allows for a better understanding of the healing process evolution and the maturation of the scar, which represent myofibroblast activity, and the buildup and maturation of collagen fibers (COELHO et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The animals were divided into three groups regarding their assessment dates (four, seven and 14 days). Half of the wounds in each group were treated with saline solution and the other half with petroleum jelly (Vaseline), typically used as mock treatments to control wound healing assays (LOPES et al, 2005;OLIVEIRA et al, 2010;NAYAK et al, 2011). After the experimental period, the animals were euthanized according to resolution nº 1000 may 12 th 2012 (CFMV).…”
Section: Animalsmentioning
confidence: 99%